PENGUKURAN KUALITAS LAYANAN DIGITAL LIBRARY TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE LIBQUAL (Studi Kasus: Perpustakaan Badan Pusat Statistik Provinsi Riau) - Era Nurvia; Angraini Anggraini (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2016)
Badan Pusat Statistict Librarys (BPS) of Riau Province has been using the system digilib since 2012 as a service for visitors to facilitate getting publications sought. However there are still some constraints on the system such as the length of the visitor searching for data and incomplete data that is causing the viewer does not get the data sought. The aim of this study was to determine the quality of the Digital Library for user satisfaction in BPS Library Riau Province In this study to measure the quality of service using Libqual method introduced by ARL (Association: Research Libraries), which consists of three dimensions namely Affect of service, Controll Information and Library As Place. Sampling technique used is accidental sampling is sampling technique by accident, anyone who by chance met the researchers can be used as a sample, if it is deemed that the person who happened to be found suitable as a data source. Questionnaires were distributed as many as 70 copies. From the research is that the overall quality of service digilib already have good quality with an average value of 3.59 Perceptions and expectations of 2.87 minimum. However, there is still a gap GAP for hope in one's ideals.